A novel prognostic model predicting overall survival in patients with metastatic castration‐resistant prostate cancer receiving standard chemotherapy: A multi‐trial cohort analysis. Issue 13 (5th July 2022) - Modonutti, Daniele; Majdalany, Sami E.; Corsi, Nicholas; Li, Pin; Sood, Akshay; Dalela, Deepansh; Jamil, Marcus L.; Hwang, Clara; Menon, Mani; Rogers, Craig G.; Trinh, Quoc‐Dien; Novara, Giacomo; et al.
Abstract: Purpose: Generalizable, updated, and easy‐to‐use prognostic models for patients with metastatic castration‐resistant prostate cancer (mCRPC) are lacking. We developed a nomogram predicting the overall survival (OS) of mCRPC patients receiving standard chemotherapy using data from five randomized clinical trials (RCTs). Methods: Patients enrolled in the control arm of five RCTs (ASCENT 2, VENICE, CELGENE/MAINSAIL, ENTHUSE 14, and ENTHUSE 33) were randomly split between training ( n = 1636, 70%) and validation cohorts ( n = 700, 30%). In the training cohort, Cox regression tested the prognostic significance of all available variables as a predictor of OS. Independent predictors of OS on multivariable analysis were used to construct a novel multivariable model (nomogram). The accuracy of this model was tested in the validation cohort using time‐dependent area under the curve (tAUC) and calibration curves. Results: Most of the patients were aged 65–74 years (44.5%) and the median (interquartile range) follow‐up time was 13.9 (8.9–20.2) months. At multivariable analysis, the following were independent predictors of OS in mCRPC patients: sites of metastasis (visceral vs. bone metastasis, hazard ratio [HR]: 1.24), prostate‐specific antigen (HR: 1.00), aspartate transaminase (HR: 1.01), alkaline phosphatase (HR: 1.00), body mass index (HR: 0.97), and hemoglobin (≥13 g/dl vs. <11 g/dl, HR: 0.41; all p < 0.05). A nomogram based on these variables was developed and showed favorable discrimination (tAUC at 12 and 24 months: 73% and 72%, respectively) and calibration characteristics on external validation. Conclusion: A new prognostic model to predict OS of patients with mCRPC undergoing first line chemotherapy was developed. This can help urologists/oncologists in counseling patients and might be useful to better stratify patients for future clinical trials.